Spreading the Experience of Preschool Educational Establishments - V. M. Dyukov (Russian State Vocational Pedagogical University, 2015)
The paper observes the issue of spreading the innovative experience of municipal preschool educational establishments (MPEE). The author outlines the ways of spreading the ideas of «Development Program of MPEE» and « Educational Program of MPEE» worked out according to the federal state requirements. Theoretical methodological basis of the research combines the fundamental studies of the last century's Russian teachers and psychologists: L. S. Vygodsky, A. N. Leontyev, L. I. Bozhovitch, A. V. Zaporozhets, V. V. Davydov, etc. Based on their studies, a series of teaching methodical manuals was developed in the Institute of Reflexive Psychology of Creativity and Humanizing the Education at the International Academy of Humanizing the Education, Sotchi-Magdeburg: «Russian Education 2020 - the Model of Preschool Education» and «Pedagogic Innovations in MPEE of Innovative Type».In author's opinion, the outcome of the research can promote the modernization efficiency in preschool education.